Pendampingan Industri Hijau Dan Fasilitas Pariwisata Kampung Batik Malon - Dyan Triana Putra; Julian Andriani Putri; Shella Gherina Saptiany (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Green Companies are a necessity for businesses to ensure sustainability in environmental management, preventing pollution and environmental damage during construction, production, or when products or services are used by customers, even up to the point of disposal. To provide satisfaction to tourists, tourist attractions must have adequate facilities to support the needs of tourists during their visit and to fulfill their expectations. Green industries and tourism play a crucial role in local economic development and environmental conservation. This study aims to provide assistance to green industries and tourism facilities in Kampung Batik Malon, focusing on sustainable development and empowerment of the local community. Assistance is provided through skills training to improve the quality of batik products and introduce environmentally friendly production techniques. In addition, the development of tourism facilities, such as homestays based on local culture and interactive batik galleries, is implemented to enhance the attractiveness of the tourist destination. Local community empowerment is carried out through participation in the decision-making process and the establishment of cooperatives to improve market access. The assistance also involves a sustainable approach to managing industrial waste and promoting environmentally friendly practices. The results of this assistance implementation show a significant increase in the quality of batik products, an increase in the number of tourist visits, and an increase in the income of the local community. Additionally, Kampung Batik Malon has successfully reduced its environmental impact through more sustainable production practices. Therefore, this activity contributes to sustainable development by demonstrating that the integration of green industries and tourism can be a successful model for strengthening the local economy while preserving the environment. Furthermore, this research provides guidance for other villages that wish to adopt a similar approach in developing the local potential of tourist attractions.